IDNLearn.com: Your go-to resource for finding expert answers. Ask any question and receive timely, accurate responses from our dedicated community of experts.
Sagot :
Let's solve each equation step-by-step and match them to their solutions.
### Equation 1: [tex]\( 4.5x - 7 = 20 \)[/tex]
Step 1: Add 7 to both sides of the equation to isolate the term with [tex]\( x \)[/tex].
[tex]\[ 4.5x - 7 + 7 = 20 + 7 \][/tex]
[tex]\[ 4.5x = 27 \][/tex]
Step 2: Divide both sides by 4.5 to solve for [tex]\( x \)[/tex].
[tex]\[ x = \frac{27}{4.5} \][/tex]
[tex]\[ x = 6 \][/tex]
So, for the equation [tex]\( 4.5x - 7 = 20 \)[/tex], the solution is:
[tex]\[ x = 6 \][/tex]
### Equation 2: [tex]\( -3x + 7 = 28 \)[/tex]
Step 1: Subtract 7 from both sides of the equation to isolate the term with [tex]\( x \)[/tex].
[tex]\[ -3x + 7 - 7 = 28 - 7 \][/tex]
[tex]\[ -3x = 21 \][/tex]
Step 2: Divide both sides by -3 to solve for [tex]\( x \)[/tex].
[tex]\[ x = \frac{21}{-3} \][/tex]
[tex]\[ x = -7 \][/tex]
So, for the equation [tex]\( -3x + 7 = 28 \)[/tex], the solution is:
[tex]\[ x = -7 \][/tex]
### Equation 3: [tex]\( 2x + 3 = -7 \)[/tex]
Step 1: Subtract 3 from both sides of the equation to isolate the term with [tex]\( x \)[/tex].
[tex]\[ 2x + 3 - 3 = -7 - 3 \][/tex]
[tex]\[ 2x = -10 \][/tex]
Step 2: Divide both sides by 2 to solve for [tex]\( x \)[/tex].
[tex]\[ x = \frac{-10}{2} \][/tex]
[tex]\[ x = -5 \][/tex]
So, for the equation [tex]\( 2x + 3 = -7 \)[/tex], the solution is:
[tex]\[ x = -5 \][/tex]
### Matching the Solutions
Now, we match each solution to its corresponding equation:
- [tex]\( (4.5x - 7 = 20) \rightarrow x = 6 \)[/tex]
- [tex]\( (-3x + 7 = 28) \rightarrow x = -7 \)[/tex]
- [tex]\( (2x + 3 = -7) \rightarrow x = -5 \)[/tex]
Thus, the solutions matched to the equations are as follows:
- [tex]\( 4.5x - 7 = 20: \quad x = 6 \)[/tex]
- [tex]\( -3x + 7 = 28: \quad x = -7 \)[/tex]
- [tex]\( 2x + 3 = -7: \quad x = -5 \)[/tex]
### Equation 1: [tex]\( 4.5x - 7 = 20 \)[/tex]
Step 1: Add 7 to both sides of the equation to isolate the term with [tex]\( x \)[/tex].
[tex]\[ 4.5x - 7 + 7 = 20 + 7 \][/tex]
[tex]\[ 4.5x = 27 \][/tex]
Step 2: Divide both sides by 4.5 to solve for [tex]\( x \)[/tex].
[tex]\[ x = \frac{27}{4.5} \][/tex]
[tex]\[ x = 6 \][/tex]
So, for the equation [tex]\( 4.5x - 7 = 20 \)[/tex], the solution is:
[tex]\[ x = 6 \][/tex]
### Equation 2: [tex]\( -3x + 7 = 28 \)[/tex]
Step 1: Subtract 7 from both sides of the equation to isolate the term with [tex]\( x \)[/tex].
[tex]\[ -3x + 7 - 7 = 28 - 7 \][/tex]
[tex]\[ -3x = 21 \][/tex]
Step 2: Divide both sides by -3 to solve for [tex]\( x \)[/tex].
[tex]\[ x = \frac{21}{-3} \][/tex]
[tex]\[ x = -7 \][/tex]
So, for the equation [tex]\( -3x + 7 = 28 \)[/tex], the solution is:
[tex]\[ x = -7 \][/tex]
### Equation 3: [tex]\( 2x + 3 = -7 \)[/tex]
Step 1: Subtract 3 from both sides of the equation to isolate the term with [tex]\( x \)[/tex].
[tex]\[ 2x + 3 - 3 = -7 - 3 \][/tex]
[tex]\[ 2x = -10 \][/tex]
Step 2: Divide both sides by 2 to solve for [tex]\( x \)[/tex].
[tex]\[ x = \frac{-10}{2} \][/tex]
[tex]\[ x = -5 \][/tex]
So, for the equation [tex]\( 2x + 3 = -7 \)[/tex], the solution is:
[tex]\[ x = -5 \][/tex]
### Matching the Solutions
Now, we match each solution to its corresponding equation:
- [tex]\( (4.5x - 7 = 20) \rightarrow x = 6 \)[/tex]
- [tex]\( (-3x + 7 = 28) \rightarrow x = -7 \)[/tex]
- [tex]\( (2x + 3 = -7) \rightarrow x = -5 \)[/tex]
Thus, the solutions matched to the equations are as follows:
- [tex]\( 4.5x - 7 = 20: \quad x = 6 \)[/tex]
- [tex]\( -3x + 7 = 28: \quad x = -7 \)[/tex]
- [tex]\( 2x + 3 = -7: \quad x = -5 \)[/tex]
Thank you for contributing to our discussion. Don't forget to check back for new answers. Keep asking, answering, and sharing useful information. IDNLearn.com is committed to providing the best answers. Thank you for visiting, and see you next time for more solutions.